Effect of Physiologic Delivery Education on Mental Health of Pregnant Women - Shohreh Ayoubi; Nabi Bostan (Golestan University of Medical Sciences, 2017)
Background: Pregnancy and postnatal period are associated with significant psychological and physiological changes, which might sometimes induce pathological variations, as well. This study aimed to evaluate the effect of physiologic delivery education on mental health of pregnant women. Methods: This clinical trial was conducted on 50 pregnant women, who were referred to three healthcare centers and Motazedi Hospital of Kermanshah, Iran, in 2015. The samples were  selected through simple random sampling and divided into two groups of intervention and control. The intervention group received eight 90-minute sessions, whereas no intervention was administered to the control group. The data collection tools consisted of a demographics form and Goldberg's General Health Questionnaire (GHQ-28), which were filled out by the participants in a pretest-posttest design. Data analysis was performed in SPSS, version 20, using analysis of covariance. Results: Given the difference in mean scores of the intervention and control groups before (23.6) and after (20.55) the intervention, it could be concluded that reduction of three scores after the training sessions was indicative of improved mental health of the participants. Thus, physiologic delivery education could enhance mental health of pregnant women (P<0.01). Conclusion: Physiologic delivery education improved mental health in pregnant women.